Design massive MIMO antenna array system using Single/Double Negative (S/DNG) metamaterial unit cells for 5G sub-6 GHz base station applications - Ibrahim, Sura Khalil; Singh, Mandeep Jit; Islam, Mohammad Tariqul; Islam, Md Shabiul; Salem, Samir; Al-Bawri (International Journal of Electronics and Telecommunications, 2026)
For 5G applications, the presented paper provides a unique integrated massive multiple input-multiple output (m- MIMO) antenna system improved with the metamaterial (MTM). The compact complementary circular split-ring resonator (CSRR) with square ring ground, broad ENG (i.e., epsilon negative metamaterial) with a bandwidth of 250 MHz, and near-zero refractive index (NZRI) qualities enable the suggested system to achieve single and double negative (S/DNG) characteristics. Operating at 3.5GHz (3.37-3.62 GHz), m MIMO antenna design consists of 4 subarrays with three layers that function inside the 5G frequency range. As opposed to conventional antennas without MTM, the antenna exhibits high port isolation between adjacent elements. Every subarray comprises eight patches, with feeding networking in the middle, partial ground on the top layer, and a full ground plan on the bottom layers. With 32 elements and a total 319 × 160 × 1.575 mm³ volume, the suggested antenna design is created and simulated. With a reflection coefficient (S11) greater than -10 dB, isolation below 39.585 dB, as well as a 10.4 dBi peak gain for every sub-array, results show that the sub-6 GHz antenna performs exceptionally well. Achieving an exceptionally low ECC (i.e., envelope correlation coefficient) of no more than 0.001 and total efficiencies in the region of >90%, along with band of 250 MHz and a 19dBi overall gain, the antenna loaded with MTM also exhibits excellent MIMO performance. The potential of the suggested antenna for cutting-edge 5G applications is highlighted by such results.